Nanoparticle-Based Lateral Flow Biosensors Integrated With Loop-Mediated Isothermal Amplification for the Rapid and Visual Diagnosis of Hepatitis B Virus in Clinical Application - Chen, Xu; Wang, Shoshi; Tan, Yan; Huang, Junfei; Yang, Xingui; Li, Shijun (Frontiers in Bioengineering and Biotechnology, 2021)
Hepatitis B virus (HBV) infection remains one of the main public health issues all over the world. Developing a rapid, sensitive, specific, easy-to-operation, and cost-saving approach for diagnose of HBV is essential for its therapy and prevention. Here, we firstly devise a novel approach, termed loop-mediated isothermal amplification integrate with nanoparticle-based lateral flow biosensor (LAMP-LFB) for detection of HBV in clinical application. The results indicated that a set of LAMP primers based on the S gene were valid for establishment of HBV-LAMP-LFB assay. The optimal HBV-LAMP amplification could be carried out at a constant temperature 65℃ for 40 min. The whole detection process, including HBV genomic DNA preparation (~10 min), HBV-LAMP amplification (40 min), and LFB readout (within 2 min), could be achieved within 60 min. The limit of detection (LoD) of the HBV-LAMP-LFB technology was 10 IU per test. The specificity of this assay was one hundred percent, and has no cross-reactions to other pathogens. Hence, these results suggested that the HBV-LAMP-LFB technique established in current study is a sensitive, rapid, specific, visual, simple and cost-saving method for screening of HBV agents. More importantly, the HBV-LAMP-LFB technology has great potential to develop a point-of-care (POC) testing in clinical application, especially in resource scarcity regions.